2005
DOI: 10.1158/1078-0432.ccr-04-1751
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Evaluation of the Pharmacodynamic Properties of 2,5-Diaziridinyl-3-Hydroxymethyl-6-Methyl-1,4-Benzoquinone

Abstract: Purpose: The purpose of our study was to investigate the cellular accumulation, DNA crosslinking ability, and cellular toxicity of RH1 (2,5-diaziridinyl-3-[hydroxymethyl[-6-methyl-1,4-benzoquinone), a novel DNA alkylating agent currently in clinical trials. In addition, the in vivo efficacy of RH1 formulated in different vehicles was also compared. Experimental Design: RH1 is activated by the two-electron reducing enzyme NQO1 [NAD(P)H:quinone oxidoreductase] forming a potent cytotoxic agent that cross-links DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Reduction of RH1 activates aziridine residues, which subsequently induce DNA damage (Cummings et al, 2003;Kim et al, 2004a;Kim et al, 2004b;Ward et al, 2005;Hussein et al, 2009). Because NQO1 is abundantly expressed in a variety of cancer tissues, it has been suggested that such tissues can be selectively damaged by RH1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reduction of RH1 activates aziridine residues, which subsequently induce DNA damage (Cummings et al, 2003;Kim et al, 2004a;Kim et al, 2004b;Ward et al, 2005;Hussein et al, 2009). Because NQO1 is abundantly expressed in a variety of cancer tissues, it has been suggested that such tissues can be selectively damaged by RH1.…”
Section: Discussionmentioning
confidence: 99%
“…Because NQO1 is abundantly expressed in a variety of cancer tissues, it has been suggested that such tissues can be selectively damaged by RH1. This enzymedirected cancer-targeting agent is currently being tested in clinical trials (Cummings et al, 2003;Kim et al, 2004a;Kim et al, 2004b;Ward et al, 2005;Hussein et al, 2009). However, the molecular mechanisms underlying the therapeutic effects of the agent on solid tumours have not yet been clearly elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RH1 is a compound selected for clinical development by the Cancer Research Campaign (CRC) and the NCI, and after its preclinical evaluation [15], it successfully underwent phase 1 evaluation [16].…”
Section: Introductionmentioning
confidence: 99%
“…These compounds are activatable by the enzyme NQO1, which is rarely expressed in most normal human tissues but is highly upregulated in many tumor cells. RH1 (compound 3), AZQ (compound 4), and TZQ (compound 5) have been shown to be effective anticancer agents in preclinical studies, with RH1 recently completing phase I trials (4,14,61). All appear to induce cell damage primarily by DNA alkylation and cross-linking following reductive activation (13,66).…”
mentioning
confidence: 99%